Validity of an Interactive E-Student Worksheet (E-LKPD) Based on Structured Inquiry Using Liveworksheets on the Reaction Rate Topic for Phase F Grade XI Senior High School - Ririn Oldia Azzahra; Minda Azhar (Darul Yasin Al Sys, 2026)
The reaction rate topic is considered one of the most challenging areas of chemistry because it involves abstract and conceptually complex principles. This study aimed to determine the validity of an interactive electronic student worksheet (E-LKPD) developed for the reaction rate topic using a structured inquiry model and the Liveworksheets platform. The study employed an Educational Design Research approach based on the Plomp model, comprising preliminary research, prototyping, and assessment phases; however, the investigation was limited to the prototyping phase, specifically Prototype III. Validation data obtained from three validators were analyzed using Aiken’s V coefficient. The findings showed an overall average Aiken’s V value of 0.96. Specifically, the E-LKPD achieved validity coefficients of 0.93 for content, 0.96 for presentation, 0.95 for language, 0.98 for graphics, and 0.99 for computer-based features, with all assessed components categorized as valid. These results indicate that the developed E-LKPD satisfies the required content, instructional, linguistic, visual, and technological validity criteria. The study contributes to the development of structured inquiry-based digital learning materials by providing a validated interactive resource for teaching reaction rates. The E-LKPD therefore has the potential to support more interactive chemistry learning and provides a foundation for subsequent studies examining its practicality and effectiveness in classroom implementation.